Words-images-words: a methodological path for teaching art (Revista Apotheke, 2024)
The first-person narrative is how to write this research, not in a personalized first person, but beyond my experiences related to my experiences. Carrying out this research involves my understanding of teaching, when I report experiences that did not distance me as an observer of this world and I situated myself as living in a place that I consider to be lands-landscapes-lands. Places embraced by the anxieties of research, of teaching, surrounded by absences, emptiness, doubts and uncertainties that are not just my characteristics, but that can be born in the encounter with the readers of this research. I explain how I create metaphors to make clear what I understand and how to think about words and images such as land and landscapes. Teaching and student experiences are lands that are taken to other spaces where they are given new meaning in places that will soon transform. I understand with Tuan (1983) that these spaces and places are not just surrounding geopolitical factors and I share the idea of social, historical and cultural living with the subjectivities of each individual. I refer to my encounter with texts that showed me how I create and appropriate words from words-images-words in a contemporary teaching perspective. In these reflective moments discovered with Magritte, in Foucault’s text (1988), through the system of verbal and visual representation in search of similarities and similarities, with Beck (2004) that the system of meanings proposes a path to possible thought. And in dialogue with Didi-Huberman (2010) I understood a little more about the interaction with the image. Thus, the proposal presented in this research presents a methodological path to think about teaching art with words-images-words.
Keywords: teaching; memory; teaching visual arts; words-images-words